Bio-electrochemical post-treatment of anaerobically treated landfill leachate - TUĞTAŞ KARNABAT, ADİLE EVREN; ÇALLI, BARIŞ (ELSEVIER SCI LTD, 2013)
Bio-electrochemical treatment of anaerobically pre-treated landfill leachate was investigated in batch and continuous-flow two-chambered microbial fuel cells (MFCs). A high strength young landfill leachate was pre-treated using an upflow anaerobic sludge blanket reactor and the effluent resembling medium-aged landfill leachate was fed to the anode chamber of MFCs. The highest maximum current and power densities achieved in continuous-flow MFC with hydraulic retention time (HRT) of five days were 525 mA/m(2) (8227 mA/m(3)) and 158 mW/m(2) (2482 mW/m(3)), respectively. Increase of HRT from one day to five days resulted in the occurrence of partial nitrification, where influent ammonia was converted into nitrite presumably due to the inhibitory effects of free ammonia. The maximum power and current densities obtained in this study were higher compared to other studies with similar leachate characteristics. The results of this study suggest that MFCs can be exploited as a polishing step for anaerobically pre-treated landfill leachate. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Landfill leachate; Microbial fuel cells; Nitrification; Power density; Volatile fatty acids; MICROBIAL FUEL-CELLS; WASTE-WATER; AIR-CATHODE; ELECTRICITY-GENERATION; REMOVAL; AMMONIA; NITRIFICATION; OPERATION; ACID